2022
DOI: 10.1530/rem-22-0007
|View full text |Cite
|
Sign up to set email alerts
|

Redox-sensitive DJ-1 protein: an insight into physiological roles, secretion, and therapeutic target

Abstract: The highly conserved DJ-1 protein fundamentally acts as a redox sensor conferring antioxidative cytoprotection under oxidative insults. DJ-1 preferentially undergoes oxidation at 106 cysteine residue (Cys106) under oxidative stress. Although initially identified as an oncogene, emerging evidence suggests the essential roles of DJ-1 in modulating numerous physiological processes involved in cellular growth, development, survival, and death. Compromised DJ-1 expression and function directly or indirectly trigger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 184 publications
0
4
0
Order By: Relevance
“…DJ-1 is up-regulated in response to oxidative insult serving as a cellular feedback mechanism to confer antioxidative defence during various physiological and pathological processes. 34 In this study, we identified overexpressing DJ-1 protein as a novel strategy for AMD and DR treatment.…”
Section: Tfnas-dj-1-sarna Protect Against Oxidative Injurymentioning
confidence: 95%
“…DJ-1 is up-regulated in response to oxidative insult serving as a cellular feedback mechanism to confer antioxidative defence during various physiological and pathological processes. 34 In this study, we identified overexpressing DJ-1 protein as a novel strategy for AMD and DR treatment.…”
Section: Tfnas-dj-1-sarna Protect Against Oxidative Injurymentioning
confidence: 95%
“…As an essential redox sensor, DJ-1 play significant roles in antioxidative cytoprotection under oxidative insult. This function of DJ-1 enables it to be involved in modulating numerous physiological processes, such as cellular growth, development, survival, and death [ 59 ].…”
Section: Non-enzymatic Functions Of Dj-1mentioning
confidence: 99%
“…One advantage of this strategy is that DJ-1 is a secretory protein mediated by microdomain and induced by the oxidation at its residue, C106 [ 77 ]. Increased levels of secreted DJ-1 (for example, into serum, plasma, and cerebrospinal fluid) have indeed been observed in patients with different types of disease, such as breast cancer, melanoma, sepsis, stroke, allergic responses, and MS [ 59 ]. Therefore, developing specific and sensitive antibodies that can recognize DJ-1 mutants and variants would be helpful for the clinical rapid diagnosis of various diseases (e.g., the establishment of DJ-1-based enzyme-linked immunosorbent assays).…”
Section: Roles Of Dj-1 In Biomedical Researchmentioning
confidence: 99%
“…With regard to diabetes mellitus, nutritional supplementation with redox bioactive compounds was proposed to prevent or ameliorate muscle loss (Lee et al 2022) and the improvement of mitochondrial function outlined as one of the primary targets of this syndrome's treatment (de Marañón et al 2022). Of interest in the neuropsychiatric field are the systematic check of the literature concerning the actual applicability of measuring defined oxysterols as markers of Alzheimer's disease (Ademowo and Dias 2022), and the reviews on the pathophysiological role of the redox-regulated protein DJ-1 in Parkinson's disease and other pathologies (Dash et al 2022), the potential therapeutic use of sirtuins in the treatment of Rett syndrome (Cordone et al 2022), an appropriate insight into the mechanisms by which hypoxic preconditioning actually attenuates neuronal oxidative stress and damage was afforded (Millán et al 2022). Finally, the impact of a major oxysterol of non-enzymatic origin, namely 7-ketocholesterol, in human pathophysiology, as well as in food science, was comprehensively examined (Ghzaiel et al 2022) and the essential role of selenium as a micronutrient, but also its toxicity at non physiological amounts, has been fully reported on by Saito (2022).…”
mentioning
confidence: 99%